A Phase I Study Evaluating the Effect of Everolimus on the Pharmacokinetics of Midazolam in Healthy Subjects1. (20th February 2013) - Urva, Shweta; Bouillaud, Emmanuel; Delaney, Rosemary; Jappe, Annette; Cheung, Wing
Abstract The selective mammalian target of rapamycin (mTOR) inhibitor everolimus has demonstrated competitive inhibition of cytochrome P450 enzyme (CYP) 3A4 in vitro; however, its influence on CYP3A4 activity in humans is unknown. This study examined the influence of everolimus on the pharmacokinetics of midazolam, a sensitive CYP3A4/5 substrate, and its 1‐hydroxy metabolite in 25 healthy male subjects. Compared with administration of oral midazolam 4 mg/day alone, coadministration with everolimus 10 mg/day increased the midazolam maximum plasma concentration (Cmax) by 25% and the area under the plasma concentration–time curve (AUC) by 30%. The Cmax and AUC of 1‐hydroxymidazolam increased by 20% and 25%, respectively. Concomitant administration of everolimus with midazolam did not change the midazolam metabolic ratio (i.e., the ratio of 1‐hydroxymidazolam AUC to midazolam AUC) or the midazolam or 1‐hydroxymidazolam terminal half‐lives (geometric mean ratios for midazolam + everolimus vs. midazolam alone of 0.96, 1.03, and 1.06, respectively). These results suggest everolimus may affect the bioavailability, but not the systemic clearance, of orally coadministered CYP3A4 substrate drugs.